2014
DOI: 10.2147/ijgm.s52413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute scrotum in our consecutive operated cases: a one-center study

Abstract: PurposeThe purpose of the present study was to evaluate the clinical history, demographic data, surgical exploration findings, and final diagnoses in all young males presenting with acute scrotum to our center.Materials and methodsThis was a descriptive–retrospective study in which all consecutive cases of acute scrotum treated in our department from March 2008 to March 2012 were evaluated.ResultsA total of 116 cases were included in the study. Out of these cases, 100 cases underwent surgical exploration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…This result is compatible not only with clinical studies [ 6 10 ] in which only scrotal exploration was evaluated, but also with clinical studies [ 11 15 ] in which surgical and medical treatments were evaluated in terms of three clinical entities. The most common reason for acute scrotum was found to be TT in five of the studies [ 6 , 7 , 9 , 12 , 15 ], TTA in three of studies [ 8 , 11 , 13 ] and EO in two of studies [ 10 , 14 ]. Interestingly, some studies have shown strangulated inguinal hernia to be the most common clinical condition [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is compatible not only with clinical studies [ 6 10 ] in which only scrotal exploration was evaluated, but also with clinical studies [ 11 15 ] in which surgical and medical treatments were evaluated in terms of three clinical entities. The most common reason for acute scrotum was found to be TT in five of the studies [ 6 , 7 , 9 , 12 , 15 ], TTA in three of studies [ 8 , 11 , 13 ] and EO in two of studies [ 10 , 14 ]. Interestingly, some studies have shown strangulated inguinal hernia to be the most common clinical condition [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
“…Also, it has been reported that the viability of the testes is very common in patients who present to the hospital after more than 10 hours, and that this requires orchiectomy in almost all cases. In these studies, testis preservation rates vary between 37 and 88% [ 9 , 10 , 13 15 ]. In the present study, we observed that the TT group presented significantly earlier (55.5% <12 h) than Group 2 (p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of orchiepididymitis among our patients were found more than some similar studies. Most reseachers have chosen their patients among those who were highly suspected of torsion [1, 2, 6]. Most of the patients (34%) were in the first year of their lives so that the number of their patients with testicular torsion were higher than patients with epididimoorchitis [1].…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsion was described firstly in 1776 by Hunter [2]. Testicular torsion is defined as a rotation of the testis around the longitudinal axis of the spermatic cord, resulting in obstruction of testicular blood flow, which accounts for 13–54% of acute scrotal disease [3].…”
mentioning
confidence: 99%
“… Evidence shows young men have poor outcomes from testicular torsion directly attributable to delay in presentation to hospital [1] . Only a third to a half of adolescents present within 6 h with testicular pain, [ 2 , 3 ] There is poor understanding of why adolescents delay in presenting with testicular pain. The authors started without an a-priori hypothesis and designed a thematic qualitative research protocol to explore the phenomena is a naturalistic setting [ 4 , 5 ] .…”
mentioning
confidence: 99%